Female labour force participation and economic development. Issue 7 (1st October 2018) - Choudhry, Misbah Tanveer; Elhorst, Paul
Abstract : Purpose: The purpose of this paper is to present a theoretical model, which is aggregated across individuals to analyse the labour force participation rate, and empirical results to provide evidence of a U-shaped relationship between women's labour force participation and economic development. Design/methodology/approach: The U-shaped relationship is investigated by employing a panel data approach of 40 countries around the world over the period 1960–2005. It is investigated whether the labour force behaviour of women in different age groups can be lumped together by considering ten different age groups. Findings: The paper finds evidence in favour of the U-shaped relationship. For every age group and explanatory variable in the model, a particular point is found where the regime of falling participation rates changes into a regime of rising participation rates. Research limitations/implications: To evaluate this relationship, microeconomic analysis with primary data can also provide significant insights. Social implications: Every country can narrow the gap between the labour participation rates of men and women in the long term. Fertility decline, shifts of employment to services, part-time work, increased opportunities in education, and the capital-to-labour ratio as a measure for economic development are the key determinants. Originality/value: In addition to the U-shaped relationship, considerable research has been carried out on demographic transition. This paper brings these two strands of literature together, by econometrically investigating the impact of demographic transition on female labour force participation given its U-shaped relation with economic development, i.e., turning points for different explanatory variables are calculated and their implications for economic growth are discussed.